Penerapan Sistem Photovoltaik Sebagai Suplai Daya Listrik Beban Pertamanan - Unggul Wibawa; Andy Darmawan (Jurnal EECCIS, 2008)
Indonesian geographical position that located at equator line and sunrays along the year, then it is appropriate to implement and use sun energies that are abundant in amount and inexhaustible. Based on that matter, then to fulfill electric needs in Indonesia and as alternative of PLN power supply, then it is appropriate for development of Photovoltaic, a process can convert sunrays into electric energy directly with aid of solar cell. The use of photovoltaic by using sun energies located in VEDC Malang as garden power supply is one example of applicative project of electric power potential development by using sun energies widely in Indonesia. From experiment and analysis, obtained break down voltage percentage with same load in photovoltaic system, the highest occurs in cloudy weather 4.76% and the lowest occurs in bright weather 4.17%. From technical standpoint, it seen that used sun module and battery are not efficient compared with existing load in VEDC Malang and from economic standpoint, cost per kWH of the system Rp 42.400,- an while from PLN electricity that is Rp 27.969,5,-. Finally, it can be concluded that the use of Photovoltaic system in VEDC Malang is not efficient yet and expensiveKeywords : Photovoltaic, effeciency, breakdown voltage